Diagnostic and prognostic value of independent and combined detection of computed tomography, ultrasound, and positron emission tomography - computed tomography in lymphoma - Lihong Shi; Haihua Hu (SLAS Technology, 2024)
Lymphoma is a malignant tumor originating from the lymphopoietic system, which can affect all tissues and organs of the body. Lymphoma is highly heterogeneous and the therapeutic effect varies greatly. Different pathological types and stages of lymphoma differ greatly in terms of treatment intensity and prognosis. Early diagnosis of lymphoma is very important to improve the prognosis of patients. Therefore, this work explored the diagnostic value of independent and combined detection of computed tomography (CT), ultrasound, and positron emission tomography - computed tomography (PET-CT) for lymphoma. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) in the PET-CT and combination groups were greatly higher than those in the CT and ultrasound groups, showing obvious differences (P < 0.05). The area under curve (AUC) values in the CT group, ultrasound group, PET-CT group, and combination group were 0.632 (P = 0.032), 0.614 (P = 0.025), 0.793 (P = 0.002), and 0.859 (P = 0.001), respectively, exhibiting observable differences (P < 0.05). the sensitivity and specificity of PET/CT for lymphoma were higher than those of CT and ultrasound, which can clearly show the early mild results of lymphatic lymphoma. Therefore, the combined diagnosis of lymphatic lymphoma with PET/CT was of high clinical value.